Comparing the Effect of Nonactivated Platelet-Rich Plasma, Activated Platelet-Rich Plasma, and Bone Morphogenetic Protein-2 on Calvarial Bone Regeneration. Issue 2 (March 2016) - Jeon, Yeo Reum; Jung, Bok Ki; Roh, Tai Suk; Kang, Eun Hye; Lee, Won Jai; Rah, Dong Kyun; Lew, Dae Hyun; Yun, In Sik
Abstract : Abstract: Although platelet-rich plasma (PRP) is widely used to enhance bone graft survival, the effect of PRP itself on bone regeneration is unclear. Because activated PRP releases many growth factors in a bolus, there are controversies regarding the effect of activation of the PRP on bone regeneration. Thus, we studied the effect of activated versus nonactivated PRP on bone regeneration and compared the effect with that of recombinant human bone morphogenetic protein-2 (rhBMP-2) in a critical-sized cranial defect model. Forty New Zealand white rabbits were randomly divided into 4 groups. Defect sizing 15 × 15 mm 2 was created on the cranium of each rabbit, and then a collagen sponge soaked with normal saline, rhBMP-2, nonactivated PRP, or PRP activated with CaCl2 solution was immediately placed on the defect. After 16 weeks, using three-dimensional computed tomography and digital photography, the volume and new bone surface area were measured. The newly created bone was histologically analyzed. The experimental groups showed a significantly increased volume and surface area of new bone compared with the control group ( P  < 0.05), but no significant differences were found among the experimental groups. Histologic examination in the experimental groups showed newly created bone that had emerged in the center as well as the margin of the defect. Overall, these results indicate that PRP enhanced bony regeneration regardless of activation with an effect that was comparable to that of rhBMP-2. Thus, PRP has therapeutic effects on bone regeneration and may replace rhBMP-2, which is costly.